2016
DOI: 10.3926/jiem.2072
|View full text |Cite
|
Sign up to set email alerts
|

ISO 9001 aspects related to performance and their level of implementation

Abstract: Abstract:Purpose: In the last three decades, thousands of companies around the world have embraced the ISO 9001 standard in their quest to improve company performance and customer satisfaction. In recent literature, a number of authors have identified different "levels" of ISO 9001implementation. This study aims to analyse these implementation levels in companies from the point of view of the customer, and provide guidelines for future improvement. Findings: Auditing suppliers plays a unique role in helping to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It was found that "Quality" is the most important criterion to be taken into consideration in the selection of a certification body, followed by "Brand and Tradition," "Management" and finally "Cost." These results demonstrate the great concern of companies to ensure the expected returns from the implementation of ISO 9001 instead of worrying about costs or forms of application in the same way observed by Dalmau et al (2016). However, it is important to note that the returns of ISO 9001 implementation are also related to internal objectives of the organization in the pursuit of certification (Valmohammadi and Kalantari, 2015;Prajogo, 2011).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It was found that "Quality" is the most important criterion to be taken into consideration in the selection of a certification body, followed by "Brand and Tradition," "Management" and finally "Cost." These results demonstrate the great concern of companies to ensure the expected returns from the implementation of ISO 9001 instead of worrying about costs or forms of application in the same way observed by Dalmau et al (2016). However, it is important to note that the returns of ISO 9001 implementation are also related to internal objectives of the organization in the pursuit of certification (Valmohammadi and Kalantari, 2015;Prajogo, 2011).…”
Section: Discussionmentioning
confidence: 63%
“…In addition, a qualified audit team also influence positively (Hamza and Alenazil, 2013). Concerning the role of auditors, Dalmau et al (2016) noted that external auditors play a crucial role in the identification of system failures that affect products and processes by identifying opportunity and suggesting areas for improvement, as well as influence on the levels of implementation of ISO 9001.…”
Section: Iso 9001-implementation and Certificationmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2012). They enable firms to identify a system weakness and identify areas for improvement (Castello Dalmau et al. , 2016).…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…Organisations started moving from one CB to another searching for reliability and value; however, no difference and improvement were observed. Reportedly, confidence diminished due to the ineffectiveness of the audit process, and lack of auditor competency, integrity and commercialisation (Castell o et al, 2016;Castka et al, 2015;Castka et al, 2020). Such challenges, which are ongoing, suggest the need to extend the TPQA beyond compliance, to add value in auditing (Lenning, 2019;Ab Wahid and Tan, 2021).…”
Section: Introductionmentioning
confidence: 99%